2019
DOI: 10.7150/jbji.37757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation One Year after DAIR Treatment in 91 Suspected Early Prosthetic Joint Infections in Primary Knee and Hip Arthroplasty

Abstract: Introduction: Early recognition and appropriate initial treatment with debridement, antibiotics and implant retention (DAIR) if a suspicion of an early prosthetic joint infection (PJI) is present can eradicate infection on first attempt and prevent implant failure. We evaluated the outcome after 1 year of patients treated with DAIR after primary total knee arthroplasty (TKA) or total hip arthroplasty (THA). Furthermore, we determined preoperative, microbiology, and treatment factors related to failure after DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
3
18
1
5
Order By: Relevance
“…In this study of patients with PJI after primary THA, DAIR with exchange of components was more successful than non-exchange DAIR. The success rates, although evaluated using a reoperation as the end point, lie within the range of previously reported rates 3 - 8 . There is existing evidence that an exchange improves success rates 4 , 8 , 11 , 13 , but it should be noted that the results were based mainly on smaller study samples.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In this study of patients with PJI after primary THA, DAIR with exchange of components was more successful than non-exchange DAIR. The success rates, although evaluated using a reoperation as the end point, lie within the range of previously reported rates 3 - 8 . There is existing evidence that an exchange improves success rates 4 , 8 , 11 , 13 , but it should be noted that the results were based mainly on smaller study samples.…”
Section: Discussionsupporting
confidence: 81%
“…Patients infected with S. aureus or S. lugdunensis had a higher risk of having a reoperation than those with a CoNS infection. CoNS infections were associated with treatment failure in a previous study 10 , but they have also been reported be associated with outcomes equal to those of S. aureus PJI 3 . We did not have access to resistance profiles of causative microbes, and our finding is difficult to explain.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…В нашей когорте из 26 пациентов с ранней послеоперационной и острой гематогенной ППИ, пролеченных по протоколу хирургической обработки с сохранением имплантата, частота контроля над инфекцией за период наблюдения 5,5 лет составила 80,8%. Полученные нами результаты успешного лечения ранней ППИ сопоставимы с результатами современных исследований, в которых авторы применяли указанный метод лечения [1, 5, 12, 13, 14, 15,16].…”
Section: Discussionunclassified